Design and optimization of a modular wireless power system based on multiple transmitters and multiple receivers architecture - Liu, Jingying; Min, Yao; Gao, Jian; Yang, Aixi; Zhou, Jing (Frontiers in Energy Research, 2022)
Wireless Power Transfer (WPT) technology has been applied to electric vehicles (EVs), for its convenience, safety, and high reliability. However, for the traditional single-transmitter-single-receiver WPT system, due to its uneven electromagnetic field distribution, the power transfer capability and the anti-offset performance are always insufficient. The multi-transmitter-multi-receiver (MTMR) WPT system based on modular inverters with coils can not only improve the transmission power of the system but also boost the system’s anti-offset ability due to its more uniform magnetic field distribution. In this study, the topology and transmission characteristics of the MTMR WPT system are discussed accordingly: 1) A decoupling method of transmitting coil based on capacitance compensation is proposed, and the particle swarm optimization algorithm is used to derive the optimal design scheme of magnetic coupling coil. 2) A phase-shifting control strategy is proposed to realize the phase synchronization and current sharing control of coil current at each transmitter. Finally, the simulation and experimental results show that the modular wireless power transfer system with multiple transmitters and multiple receivers has strong power transmission capability and anti-offset performance.